Improving the Motivation to Learn the Quran Surah At-Tin of Grade IV Students of Elementary School 20 Kampung Padang through the Cooperative Learning Model - Utama, Ferida (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning motivation in Islamic religious education learning by using a cooperative learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the cooperative learning model can improve student learning motivation in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 53.41%, the first cycle 67.19% and in the second cycle it increased to 90.13%. Thus, the use of student cooperative learning models can be used as an alternative to improve student learning motivation in Islamic religious education learning.